Rôle des Institutions dans le Développement Économique: Role of Institutions in Economic Development - Akacem Kada; Selka Asma (Journal of North African Economies, 2025)
institutions are of paramount importance for the social stability and cohesion of a country. The purpose of our article is to show that especially in the economic field, the importance of institutions is paramount and that they play a vital role in the economic development of a country.